The Effects of Post Weld Heat Treatment on Microstructure and Mechanical Properties of API X70 Linepipe using Submerged Arc Welding - Minha Park; Gang Ho Lee; Gwangjoo Jang; Hyoung-Chan Kim; Byoungkoo Kim; Byung Jun Kim (Archives of Metallurgy and Materials, 2024)
API X70 steel requires high strength and toughness for safety in extreme environments like high pressure and low temperature. Submerged Arc Welding (SAW ) is effective for manufacturing thick steel pipes. However, the welding heat input during SAW alters the microstructure and mechanical properties of the heat affected zone (HAZ). Therefore, investigating the correlation between microstructure and mechanical properties in welded X70 pipes is important to address potential degradation of HAZ and weld metal (WM). In this study, post weld heat treatment (PWHT) was performed to improve mechanical properties of HAZ and WM and to reduce residual stress caused by the welding process. We performed PWHT at 640°C for 15 hours and followed by air cooling. After heat treatment, we observed the microstructure through OM and SEM analysis, and investigated the mechanical properties through tensile test, hardness test, and Charpy impact test.